Intussusception induced by gastrointestinal metastasis of malignant melanoma: A case report. (2020) - Kumano, Koichiro; Enomoto, Tsuyoshi; Kitaguchi, Daichi; Owada, Yohei; Ohara, Yusuke; Oda, Tatsuya
Highlights: Diagnosis of intestinal metastasis of malignant melanoma is difficult because it usually made after appearing symptoms of bowel obstruction. Emergency surgery for malignant melanoma of small intestine are often performed without enough examination preoperatively. Malignant melanoma tends to metastases to the small intestine simultaneously and multiply. When treating small intestinal metastasis of malignant melanoma, location and number of the metastasis should be understood. Abstract: Introduction: Malignant melanoma sometimes metastasizes to small intestine, and could cause various clinical symptoms, including intussusception. Among the acute abdomen cohort in Japan, it is quite rare to encounter this entity. Presentation of case: A 68-year-old male patient was admitted to our hospital with chief complaints of abdominal pain and vomiting. He underwent tumor resection for malignant melanoma of the primary lesion at left foot base, local recurrence and brain metastasis during the last five years. At admission, abdominal X-ray demonstrated small bowel obstruction. An ileus tube was inserted, and contrast media enema study showed crab-like shadow defect was observed in the advanced part. Enhanced computed tomography showed intussusception in the proximal jejunum caused by a tumor of 5 cm in diameter in the advanced part. No other intestinal lesion was found. Diagnosis of intussusception caused by solitary metastasis of malignant melanoma was made. Laparoscopic partial resection of the small intestine was performed. Postoperative course was uneventful, and patient was followed in outpatient clinic without further treatment with any recurrence of disease for one years. Discussion: Malignant melanoma tends to metastases to the small intestine simultaneously and multiply. It bothers surgeons to decide range of small intestinal resection at emergency surgery. In the present study, preoperative examination allowed the adequate range of intestinal resection including location and number of metastases before operation. Conclusion: When an acute abdomen caused by intestinal metastasis of malignant melanoma was consulted, surgeon should make effort to identify location and number of metastatic lesion, preoperatively.